Characteristics of fired bricks with co-combustion fly ashes. (March 2016) - Leiva, C.; Arenas, C.; Alonso-fariñas, B.; Vilches, L.F.; Peceño, B.; Rodriguez-galán, M.; Baena, F.
Abstract: This paper studies the feasibility of utilizing co-combustion fly ashes for the production of eco-friendly fired bricks. The fly ashes from co-combustion of coal and pet coke in a Spanish Power Plant were used as raw material to replace clay to make fired bricks. The effect of fly ash with high replacing ratio (from 0 to 80%) of clay on properties of bricks was analysed. The specimens, cylinders with 32.5 mm diameter and 50 mm length, were manufactured by compressing at 10 MPa. Different firing temperatures, 800, 900 and 1000 °C, were studied. The fired bricks with high volume ratio of fly ash present a high compressive strength and a low water absorption capacity. With increase in firing temperature, the compressive strength increased and the water absorption decreased. With increase in replacing ratio, the compressive strength decreased and the water absorption ratio increased. The bricks no present environmental problems according to the leaching study. Highlights: Producing fired brick utilized co-combustion fly ash instead of traditional clay. Performance of bricks was good and promising. The temperatures and content of fly ash on the properties of bricks were studied. No leaching problems.